Soliton and Periodic Wave Solutions of the Nonlinear Loaded (3+1)-Dimensional Version of the Benjamin-Ono Equation by Functional Variable Method (Journal of Nonlinear Modeling and Analysis, 2024)
In this article, we establish new travelling wave solutions for thenonlinear loaded (3+1)-dimensional version of the Benjamin-Ono equation bythe functional variable method. The performance of this method is reliableand effective and the method provides the exact solitary wave solutions andperiodic wave solutions. The solution procedure is very simple and the traveling wave solutions are expressed by hyperbolic functions and trigonometric functions. After visualizing the graphs of the soliton solutions and theperiodic wave solutions, the use of distinct values of random parameters isdemonstrated to better understand their physical features. It has been shownthat the method provides a very effective and powerful mathematical tool forsolving nonlinear equations in mathematical physics.